Development of mobile application for reporting suspected adverse drug reaction - Cuenco, Kimberly Faye P.; Robles, Yolanda (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2021)
Despite the presence of the pharmacovigilance system, underreporting is still a persisting problem. Therefore, the study intended to develop, implement and evaluate a mobile Software application to submit voluntary reports of medication-related problems. engineering process employed Waterfall Model involving requirement gathering and analysis, system interface design, implementation, integration and testing. Heuristic evaluation provided a baseline of user interface issues and preliminary design recommendations focusing on the principles of Eror Prevention and Correction, Flexibility and Efficiency of Use, Help User Recognizing, Diagnosing and Recovering fromn Erors and Help and Documentation. After the issues were resolved, ALARMA was deployed for beta testing in residential aged care facilities, where 69 reports were gathered. Quasi experimental design with mixed method approach involving quantitative survey and qualitative email interview evaluated the outcomes of the intervention. Positive acceptance of ALARMA due to the perceived usefulness, ease of use and satisfaction was obtained. However, to enhance users neutral perception of effectiveness and reliability towards the technology-based intervention, continuous system usage to build proficiency should be considered. Provided that the identified organizational barriers were prevented or resolved and technological factors were satisfied, there is a high possibility that ALARMA could be sustained in DOH-accredited hospitals.
Thesis (Master of Science in Pharmacy)--University of the Philippines Manila, July, 2021.
Keywords: Mobile Applications -- Development; Mobile applications -- Adverse drug reactions -- Report. -- Philippines